The efficacy of non-hormone therapy for atrophic vaginitis in postmenopausal women - M.R. Narimanova; Saprykina L.V (LCC «Medicine-Inform», 2019)
M.R. Narimanova, L.V. Saprykina N.I. Pirogov Russian National Research Medical University, Moscow, Russian Federation Aim: to assess the efficacy of non-hormonal treatment for atrophic vaginitis in postmenopausal women. Patients and Methods: 36 postmenopausal women aged 48-54 years were enrolled in this pilot comparative study. All women were subdivided into three groups. In group I (n=14), intravaginal cream with 0.5 mg of estriol was prescribed. In group II (n=10), non-hormonal multicomponent plant medication (intimate hygiene cream "Antic") was prescribed. In group III (n=12), women have refused any treatment. At baseline and after 20 and 90 days of the treatment, Vaginal Health Index Score (VHIS) and subjective signs of atrophic vaginitis were evaluated. Descriptive statistics was used to assess demographic and clinical data. Mann-Whitney U-test was used to evaluate intergroup differences. Differences were considered significant at p<0.05. Results: after 20 days, VHIS has increased in group I (16.64±0.2) and group II (14.08±0.42) as compared with group III (11.92±0.38) (р<0.05) while vaginal pH has reduced in group I (5.18±0.08) and group II (5.62±0.94) as compared with group III (6.23±0.05) (р<0.05). After 90 days, subjective signs of atrophic vaginitis have significantly improved in group I and group II as compared with baseline (р<0.05). Conclusion: increase in VHIS and improvement of subjective signs of atrophic vaginitis after 90 days have demonstrated that the treatment is effective. Therefore, non-hormone therapy may be considered as an alternative to vaginal estrogens which reduces atrophic vaginitis symptoms in postmenopausal women, in particular, in contraindications to hormone treatment or patient's unwillingness. Keywords: postmenopause, estriol, non-hormonal therapy, menopausal hormone therapy, atrophic vaginitis, genitourinary syndrome of menopause, Vaginal Health Index Score, dyspareunia, treatment, Antic. For citation: Narimanova M.R., Saprykina L.V. The efficacy of non-hormone therapy for atrophic vaginitis in postmenopausal women. Russian Journal of Woman and Child Health. 2019;2(3):257-261.